2017
DOI: 10.1002/mawe.201600753
|View full text |Cite
|
Sign up to set email alerts
|

Cooling slope casting of cast iron

Abstract: The aim of the present work is to study the effect of semi‐solid processing using cooling slope method on the microstructure and mechanical properties of grey cast iron. A water cooled castable cement coated steel plate with a variable inclination angle is used to make a mechanical treatment on the semi‐solid flow of grey cast iron. The experiment is repeated for three different pouring temperatures and three inclination angles. The tensile test, hardness test and microstructure examination is used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Additionally, microstructure with mechanical characteristics of squeeze cast a356 alloy produced via vibrating CS was also examined [24]. Studies on microstructures of cast iron produced via cooling slope are also reported [25]. Studies on structural characteristics of CS cast ZCuSn10P1 alloy were also described [26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, microstructure with mechanical characteristics of squeeze cast a356 alloy produced via vibrating CS was also examined [24]. Studies on microstructures of cast iron produced via cooling slope are also reported [25]. Studies on structural characteristics of CS cast ZCuSn10P1 alloy were also described [26].…”
Section: Introductionmentioning
confidence: 99%